Advances in the characterization of the Scorpaena plumieri cytolytic toxin (Sp-CTx). (August 2018) - Malacarne, Pedro F.; Menezes, Thiago N.; Martins, Cleciane W.; Naumann, Gustavo B.; Gomes, Helena L.; Pires, Rita G.W.; Figueiredo, Suely G.; Campos, Fabiana V.
Abstract: Proteins that account for the hemolytic activity found in scorpaeniform fish venoms are responsible for the majority of the effects observed upon envenomation, for instance, neurotoxic, cardiotoxic and inflammatory effects. These multifunctional toxins, described as protein lethal factors and referred to as cytolysins, are known to be extremely labile molecules. In the present work, we endeavored to overcome this constraint by determining optimal storage conditions for Sp-CTx, the major bioactive component from the scorpionfish Scorpaena plumieri venom. This cardiotoxic hemolytic cytolysin is a large dimeric glycoprotein (subunits of ≈65 kDa) with pore-forming ability. We were able to establish storage conditions that allowed us to keep the toxin partially active for up to 60 days. Stability was achieved by storing Sp-CTx at −80 and −196 °C in the presence of glycerol 10% in a pH 7.4 solution. It was demonstrated that the hemolytic activity of Sp-CTx is calcium dependent, being abolished by EDTA and zinc ions. Furthermore, the toxin exhibited its maximal hemolytic activity at pH between 8 and 9, displaying typical N- and O- linked glycoconjugated residues (galactose (1–4) N-acetylglucosamine and sialic acid (2–3) galactose in N- and/or O-glycan complexes). The hemolytic activity of Sp-CTx was inhibited by phosphatidylglycerol and phosphatidylethanolamine, suggesting a direct electrostatic interaction lipid - toxin in the pore-formation mechanism of action of this toxin. In addition, we observed that the hemolytic activity was inhibited by increasing doses of cholesterol. Finally, we were able to show, for first time, that Sp-CTx is at least partially responsible for the pain and inflammation observed upon envenomation. However, while the edema induced by Sp-CTx was reduced by pre-treatment with aprotinin and HOE-140, pointing to the involvement of the kallikrein-kinin system in this response, these drugs had no significant effect in the toxin-induced nociception. Taken together, our results could suggest that, as has been already reported for other fish cytolysins, Sp-CTx acts mostly through lipid-dependent pore formation not only in erythrocytes but also in other cell types, which could account for the pain observed upon envenomation. We believe that the present work paves the way towards the complete characterization of fish cytolysins. Highlights: Biological activity of Sp-CTx can be preserved for up to 60 days at −80 and −196 °C in the presence of glycerol 10%, pH 7.4. The hemolytic activity of Sp-CTx is Ca 2+ -dependent and reaches its highest levels at pH between 8 and 9. The hemolytic activity of Sp-CTx was inhibited by phosphatidylglycerol, phosphatidylethanolamine and cholesterol. Sp-CTx exhibits typical N- and O- linked glycoconjugated residues. Sp-CTx provokes edema and nociception, the former being partially inhibited by aprotinin and HOE-140.